Economic structure and development : essays in honour of Jan Tinbergen - Tinbergen, Jan; Bos, Hendricus Cornelis; Linnemann, Hans; Wolff, Pieter de (Amsterdam : New York : North-Holland Pub. Co. , American Elsevier Pub. Co., 1973)
This volume of essays is offered to Jan Tinbergen on the occasion of his retirement from his Chair at the Netherlands School of Economics, now Erasmus University, Rotterdam.
Includes bibliographical references.
oo 20/9/2018
Loans
Keywords: Economics; Economic development; Economic policy